A STUDY ON EFFECT OF DRUG DURING IN CLINICAL MANAGEMENT OF DIABETES - Khushboo; Yogesh Sharma (Journal of Biomedical and Pharmaceutical Research, 2020)
Diabetes is defined as a state in which homeostasis of carbohydrate, protein and lipid metabolism is improperly regulated as a consequence of a relative or absolute deficiency of insulin secretion, resistance to insulin action or both at one or more center in tedious pathways of hormones activity. Diabetes is deadly disease in both developed and developing countries. In 2000, there were a probable 175 million people with diabetes universal and by 2030, the projected estimate of diabetes is 354 million. The most widely recognized unfavorable responses to insulin are weight addition and hypoglycaemia (Henry et al, 1993; Kudlacek et al, 1992). Weight increase in the wake of beginning insulin treatment for uncontrolled diabetes is an inescapable outcome and is the consequence of expanded truncal fat and muscle mass and severe side effects of biguanides include diarrhoea, abdominal discomfort, nausea, metallic taste, and anorexia. Keywords: Diabetes, Insulin, Biguanides and Hypoglycaemia